Development of transesterification model for safe technology of chemical modification of oxidized fats - Korchak, Mykola; Bragin, Oleksandr; Petrova, Olena; Shevchuk, Natalia; Strikha, Liudmyla; Stankevych, Serhii; Svishchova, Yana; Khimenko, Natalia; Filenko, Olesya; Petukhova, Olena (Eastern-European Journal of Enterprise Technologies, 2022)
The object of research is the process of chemical transesterification of palm olein with increased oxidation indicators in the presence of potassium glyceroxide catalyst. Transesterification is an important method of fat modification. The use of fats with increased oxidation indicators leads to the deactivation of common catalysts and a decrease in the efficiency of the process. There is a need to increase the dosage of catalysts, increase the process temperature, which negatively affects the product quality. An alternative transesterification catalyst (potassium glyceroxide) was used for the transesterification of palm olein with increased oxidation indicators. Palm olein (CAS Number 93334-39-5) with standard indicators was used: melting point 22.4 °C, peroxide value 0.8 ½ O mmol/kg, anisidine value 0.3 c. u. Olein was subjected to heating at a temperature of 90 °C in order to increase oxidation indicators, after which it underwent transesterification. The difference in melting points of the initial and transesterified palm olein was used as a parameter of process efficiency. The maximum limit values of the oxidation indicators at which the process is effective are: peroxide value 12.7 ½ O mmol/kg, anisidine value 10.4 c. u. The difference in melting points is 12.1 °C, which indicates the efficiency of the process. The qualitative indicators of the obtained transesterified fat indicate compliance with DSTU 4336 (CAS Number 97593-46-9): melting point 34.5 °C, peroxide value 1.2 ½ O mmol/kg, anisidine value 1.0 c. u. The results of the research make it possible to use fat with increased oxidation indicators without pretreatment and predict the efficiency of transesterification depending on the fat indicators. This will increase profitability and reduce production waste.